(untitled) (Universal International Scientific Journal, 2026)
Today, dangerous natural processes are occurring in almost all parts of the Earth in varying degrees of intensity and scale. This article examines the types, factors of origin, and geographical distribution of dangerous earthquakes of natural origin using the example of the Namangan region. Also, a table of relatively strong earthquakes that occurred during 2000-2020 was analyzed, and areas with high earthquake risk in the Namangan region and adjacent areas were identified.